2014
DOI: 10.1016/j.molcel.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Selective Protein Denitrosylation Activity of Thioredoxin-h5 Modulates Plant Immunity

Abstract: In eukaryotes, bursts of reactive oxygen and nitrogen species mediate cellular responses to the environment by modifying cysteines of signaling proteins. Cysteine reactivity toward nitric oxide (NO) leads to formation of S-nitrosothiols (SNOs) that play important roles in pathogenesis and immunity. However, it remains poorly understood how SNOs are employed as specific, reversible signaling cues. Here we show that in plant immunity the oxidoreductase Thioredoxin-h5 (TRXh5) reverses SNO modifications by acting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
121
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(125 citation statements)
references
References 40 publications
4
121
0
Order By: Relevance
“…This result explains why treatment with N6022 aggravated leaf damage in plants subjected to chilling stress. Our iTRAQ data indicated that thioredoxin m (gi|222843925) was induced by cold treatment, and Kneeshaw et al (2014) reported that the Arabidopsis oxidoreductase thioredoxinh5 (TRXh5) showed a selective protein denitrosylation activity to modulate plant immunity. We also detected the effect of thioredoxin on the cold-induced protein S-nitrosylation status.…”
Section: Controlling No Metabolism Affects Defense-related Protein Acmentioning
confidence: 79%
See 1 more Smart Citation
“…This result explains why treatment with N6022 aggravated leaf damage in plants subjected to chilling stress. Our iTRAQ data indicated that thioredoxin m (gi|222843925) was induced by cold treatment, and Kneeshaw et al (2014) reported that the Arabidopsis oxidoreductase thioredoxinh5 (TRXh5) showed a selective protein denitrosylation activity to modulate plant immunity. We also detected the effect of thioredoxin on the cold-induced protein S-nitrosylation status.…”
Section: Controlling No Metabolism Affects Defense-related Protein Acmentioning
confidence: 79%
“…9c), which could explain why long-term cold stress reduces GSNOR activity. Recently, Kneeshaw et al (2014) reported that the Arabidopsis oxidoreductase thioredoxin-h5 (TRXh5) reverses SNO modifications by acting as a selective protein-SNO reductase. Thioredoxin is a class of small redox proteins and plays a role in many important biological processes including redox signaling, and it acts as antioxidant by facilitating the reduction of other proteins by cysteine thioldisulfide exchange.…”
Section: Discussionmentioning
confidence: 99%
“…2B). 22,23 These differences could be because ssi2, nox1 and gsnor1 plants either accumulate different levels of NO, or accumulate NO in different subcompartments that produces a different effect. As in vertebrates, 24 the signaling role of NO and ROS in plant SAR is concentration dependent.…”
mentioning
confidence: 99%
“…Oxidation of a single cysteine implies that rather than a disulfide, catalase may contain an S-nitrosothiol or sulfenic acid. Although the ability of NRX1 to reduce these modifications has not yet been demonstrated, they are targeted by conventional TRX family members (31)(32)(33). Regardless of these particulars, this study clearly demonstrates that NRX1-mediated reduction of catalase is an important mechanism for sustaining maximal catalase activity.…”
Section: Discussionmentioning
confidence: 73%